Breaking Bad News to a Terminally-Diseased Physician in ICCU: A Case Study of Ethical and Cultural Dilemma - Putra, Teuku Muhammad Haykal; Apriansyah, Fadhil Pratama; Putra, Bayushi Eka; Firmanda, Wibisono; Tedjasukmana, Firman; Juzar, Dafsah Arifa (Jurnal Kardiologi Indonesia, 2025)
Background: Breaking bad news is one of the most problematic tasks for physician. Moreover, local guidelines or recommendations about this is not well established in Indonesia and its practice still varies between physicians.Case Illustration: This paper presents a case of a fellow physician admitted to ICCU with terminal cardiac condition whose family wished to keep the bad news away from the patient. The physician team were in a difficult situation when the patient asked about his condition, but they decided to respect and commit to the family’s decision to not giving information about his terminal state.Conclusions: In performing such problematic task, balancing non-maleficence and autonomy principle is the key. Cultural background differences should also be considered when dealing with such cases. Other important factor that can affect this practice is lack of legal support in Indonesia. Combination of all those factors should always be considered for the best interest of both parties.